Capacity, Participation and Values in Comparative Legal Perspective - Kong, Camillia; Coggon, John; Cooper, Penny; Dunn, Michael; Ruck Keene, Alex (Bristol University Press, 2023)
With contributions from an international team of experts, this collection provides a much-needed international, comparative approach to mental capacity law. The book focuses particularly on exploring substantive commonalities and divergences in normative orientation and practical application embedded in different legal frameworks. It draws together contributions from eleven different jurisdictions across Europe, Asia and the UK and explores what productive or unproductive values and practices currently exist.